Perancangan Sistem Informasi Servis di Toko Oz Computer Salatiga Menggunakan Metode Prototype Berbasis Web - Andika, Awan Pijar; Sediyono, Eko (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Since the pandemic, there has been an increase in the frequency with which people use gadgets like computers and laptops because an increasing number of tasks can now be completed virtually. Naturally, this increases the likelihood that electronics like laptops and computers will sustain damage. Oz Computer Salatiga which provides laptop and computer services experienced an increase in customer services request due to the pandemic situation. As a result of the growing number of customers, Oz Computer Salatiga occasionally has trouble gathering information, recording the information, and notifying customers of service updates. This study will use the prototype method as a software development technique to create a web-based service information system at the Oz Computer Salatiga shop in order to solve these issues. It is hoped that this service information system will assist the Oz Computer Salatiga shop in optimizing data collection, recording, and notification of service information to customers.